2017
DOI: 10.1007/s13670-017-0196-y
|View full text |Cite|
|
Sign up to set email alerts
|

Management of Osteoporotic and Neuropathic Ankle Fractures in the Elderly

Abstract: Purpose of ReviewTreatment of osteoporotic and neuropathic ankle fractures in the elderly is challenging. The purpose of this paper is to review recent publications on this topic and to identify the optimal treatment for these fractures.Recent FindingsTreatment consists of a variety of conservative or operative options all with advantages and disadvantages as described in this review. Little research has been published that specifically focuses on elderly patients with ankle fractures. Operative treatment has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…Open reduction and internal fixation is required in all other more severe cases, in order to obtain a mechanically stable situation and restore the joint's functionality. For elderly patients who require early mobilization, the fracture fixation needs to be stable enough to allow immediate weight-bearing [61]. Depending on the type and severity of the fracture, stability can be achieved by internal fixation with plate osteosynthesis, intramedullary nailing, lag screws, or a combination thereof (Fig.…”
Section: Ankle Fracturesmentioning
confidence: 99%
See 1 more Smart Citation
“…Open reduction and internal fixation is required in all other more severe cases, in order to obtain a mechanically stable situation and restore the joint's functionality. For elderly patients who require early mobilization, the fracture fixation needs to be stable enough to allow immediate weight-bearing [61]. Depending on the type and severity of the fracture, stability can be achieved by internal fixation with plate osteosynthesis, intramedullary nailing, lag screws, or a combination thereof (Fig.…”
Section: Ankle Fracturesmentioning
confidence: 99%
“…In general, the management of ankle fractures in elderly people with osteoporosis needs to be individually considered and the decision-making process can be based on functional demands and the presence of comorbidities with a primary aim of functional restoration allowing early post-operative mobilization [61].…”
Section: Ankle Fracturesmentioning
confidence: 99%
“…15 The conventional treatment methods routinely used (including conservative management, or internal fixation), often provide poor outcomes and risk significant complications (such as non-union/malunion, fixation failure, and DVT) when applied within the geriatric population. 3 This is often multifactorial and can be a result of poor quality skin and soft tissues, osteoporosis and decreased holding strength, and poor mobility. 3,4,16 Recently, HFN has been utilized for the treatment of these osteoporotic ankle fractures.…”
Section: Discussionmentioning
confidence: 99%
“…However, for fragility ankle fracture that affects patients older than 65 years of age, the aim of surgery is to restore mobility, preserve function and to prevent complications related to non-weight-bearing. [3][4][5][6] Achieving and maintaining anatomical reduction is often difficult due to the complex fracture pattern associated with fragility ankle fractures. 7,8 Following the successful reduction in plaster, Willett, Hearn, & Cuncins observed that these injuries often went on to lose reduction and drift into valgus malalignment, thus increasing the likelihood of developing a malunion or non-union.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation